Excesso de peso em região do nordeste brasileiro: contraste entre escolares de rede pública e privada de ensino - Brasil, Lana do Monte Paula (2007)
The prevalence of obesity has been increased in the last three decades. It is already considered as epidemic by the World Health Organization and reaches around 300 million people worldwide. The weight gain in all ages is related to a sedentary way of life and hyper caloric food ingestion at the modern society. Obesity is a chronic disease and leads to high blood pressure, diabetes, cardiovascular diseases and cancer. The aim of this study was to evaluate the prevalence of weight excess among student in Natal schools and to analyze its association with age, gender, school category and geographic localization in city zones. This was a transversal study which enrolled 1927 children. 1084 of these were between 6 and 8 years-old (group 1) and 843 were 9 to 10 years-old (group 2). 895 of the total children studied in private schools and 1032 studied in public schools. 33,6% of the students had body mass index equal or above the 85th percentile and were considered as having weight excess. There was no statistical difference in this prevalence considering neither gender nor age. The weight excess prevalence in private schools was 54,5% and in public ones was 15,6% (p<0,01; OR=6,49). Weight excess was also more prevalent in the south and east city zones (41,3%) which have better quality of life index than in the north and west zones (28,4%) (p<0,01). In conclusion, the weight excess prevalence among students is found to be high in Natal and programs of intervention and prevention of obesity are necessary. The higher prevalence in private schools as in the wealthier city zones reflects the link between obesity and high socioeconomic level found in countries in developing. This was an interdisciplinary work with participation of epidemiology, child nutrition and pediatric endocrinology following the recommendations and principles of the Post graduation Program in Health Sciences of the Federal University of Rio Grande do Norte